Traumatism of Popliteal Artery in Dislocations of Knee: uso preventivo del procedimiento de Noble - Perdomo, Roberto; Pereyra Borrelli, César (Cirugía del Uruguay, 1981)
A review of traumatisms of popliteal artery in knee dislocations, shows that in 30 % of cases there is lesion of artery.